
(∀x)(Sx
→ Rx)

(∃x)(Sx · ~Px)

(∃x)(Cx · Px)

(∀x)(Ex
→ Sx)

(∀x)(Sx
→ Ex)
Compare the answers to 4 and 5; note how the 'all' and 'only' propositions are the converse of one another.

(∀x)(Vx
→ Px)
 If you wrote (∀x)(Px → Vx), then you'd be saying that all (not only) property owners may vote.

(∀x)(Ux
→ Sx)

(∀x)(Ux
→ Ex)

(∀x)(Gx
→ ~Ax)
 The speaker of this proverb undoubtedly meant that we should
not be misled by glitter to think that we have found gold. This truth
requires a 'not all' rather than an 'all not', and should be translated
~(∀x)(Gx → Ax) or (∃x)(Gx · ~Ax).

(∀x)(Dx
→ Bx)

(∃x)(Vx · ~Sx)

(∀x)(Vx
→ ~Sx), or ~(∃x)(Vx · Sx)

(∀x)(Hx
→ ~Ex)

(∃x)(Sx · Ix · Hx)

(∀x)[Cx
→ (~Wx ▼ Sx)]

(∃x)[Mx · (Dx
→ Ex)]
 We avoid (∃x)[(Mx · Dx) → Ex] because it is an existentially quantified conditional. It is equivalent to (∃x)[~(Mx · Dx)
Ex] which asserts that there is something that is either not a
dangerous medicine (like my chalk) or that is taken in excessive
amounts (like logic courses).

(∀x)[(Fx
▼ Vx) → (Wx · Dx)]
 Note how the "and" between fruits and vegetables is translated as a disjunction.

(∀x)[Ex
→ (~Mx ▼ ~Lx
▼ Fx)]

(∀x)[Px
→ [Gx « (Wx · Ex)]]

(∀x)[(Ix · Ux)
→ (Px ▼ Fx)]

(∃x)(Ax · Fx · ~Tx)

(∀x)[Gx
→ [(Wx · Ex) → Hx]
 This is equivalent to (x)[(Gx · Wx · Ex) → Hx] by exportation.

(∃x)(Px · Tx · ~Hx)

(∀x)[(Ax · Ox)
→ (Dx → ~Rx)]
 This is equivalent to (∀x)[(Ax · Ox · Dx)
→ ~Rx] by exportation.
 It is not equivalent to (∀x)~[(Ax · Ox · Dx)
→ Rx].